Pregnancy screening strategies for potentially challenging patients before diagnostic nuclear medicine procedures: qualitative survey analysis. - James, Daphne J; Cardew, Paul; Warren-Forward, Helen M (Journal of Nuclear Medicine Technology, 2013)
Because of the ionizing radiation used in diagnostic nuclear medicine procedures, it is recommended that all female patients of childbearing age be questioned about their pregnancy status before the procedure begins. Several patient groups have been identified as potentially difficult to question: teenagers, unconscious or sedated patients, patients with language or cultural barriers, and patients with mental disability. Our aim was to capture the thoughts and opinions of nuclear medicine personnel in Australia and New Zealand regarding pregnancy screening strategies before diagnostic imaging procedures. METHODS: Members of the Australian and New Zealand Society of Nuclear Medicine were invited to complete an online survey. Section 4 consisted of open-response questions asking participants to describe the strategies they use to question a patient about pregnancy status in 4 potentially difficult clinical scenarios. The content of the responses was analyzed. RESULTS: For each question, 232 responses were recorded. The most commonly used strategies included questioning teenage girls away from their parents, referring to medical notes for unconscious patients, using an interpreter and visual aids for patients with language barriers, and asking a caregiver or relative of mentally disabled patients. Pregnancy testing was used when there was doubt about the patient's pregnancy status. Personal questions about menstrual and sexual history were often asked to determine the risk of pregnancy. CONCLUSION: The study revealed that a variety of strategies are used by nuclear medicine personnel in Australia and New Zealand to determine the pregnancy status of patients. A standardized practice guideline may be useful to ensure a consistent approach to questioning that would optimize the accuracy of pregnancy assessment and reduce the possibility of fetal irradiation.